The advisability of oral health education of patients treated with fixed orthodontic appliances - Czaplińska, Joanna; Pobol-Aidi, Małgorzata; Aidi, Nedal; Matthews-Brzozowska, Teresa (Polish Journal of Public Health, 2013)
Introduction. Oral health contributes much to people’s quality of life. Proper oral hygiene is one of the most important methods of preventing the development of caries and periodontopathy.Aim. The aim of the study was to evaluate the impact of providing oral health instructions to orthodontic patients once and more frequently in a 2-year study.Material and methods. The study group consisted of 60 patients with malocclusion aged 10-20 years. The patients were divided into 2 groups: group A – patients with malocclusion treated using fixed dental appliances to whom dental hygiene instructions were provided on a regular basis, group B – patients with malocclusion treated using fixed dental appliances to whom dental hygiene instructions were provided only once. Group A received dental hygiene instructions at several points in time (T0, T1, T2, T3, T4 and during check-up appointments), whereas group B was presented with the instructions at T0 only. The study was performed using the plaque indices PlI and API, and the gingival indices GI and SBI. The differences between the groups were evaluated using the ANOVA test and the NIR value.Results. It has been confirmed that correct form of providing information about oral hygiene to patients undergoing orthodontic treatment with fixed orthodontic appliances and regular contact with the patients during check-up appointments is beneficial for the state of periodontium and oral hygiene in general. For this reason, it decreases the risk of complications during orthodontic treatment.Conclusions. Orthodontic treatment is not detrimental to oral health provided that comprehensive oral hygiene instructions are given to the patient.